2014
DOI: 10.1016/j.actamat.2014.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation in nanoindentation of tantalum: A new mechanism for prismatic loop formation

Abstract: The mechanisms of deformation under a nanoindentation in tantalum, chosen as a model body-centered cubic (bcc) metal, are identified and quantified. Molecular dynamics (MD) simulations and indentation experiments are conducted for [1 0 0], [1 1 0] and [1 1 1] normals to surface orientations. The simulated plastic deformation proceeds by the formation of nanotwins, which rapidly evolve into shear dislocation loops. It is shown through a dislocation analysis that an elementary twin (three layers) is energeticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 46 publications
5
65
2
1
Order By: Relevance
“…[26] to be least sensitive to indenter diameter and indentation velocity. On the other hand, the EAM potential function of Ravelo et al [23] has been tested during nanoindentation [13] as well as shock compression experiments [23] and the outcome suggests that this potential function is better in predicting the high pressure and high temperature phases of Ta. Since the intent of this work is to understand the deformation behaviour of Ta, this study made use of an EAM potential (Ta-1) developed by Ravelo et al [23] primarily to study extreme conditions of temperature and pressure such as during nanoindentation.…”
Section: Molecular Dynamics Simulation Of Nanoindentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] to be least sensitive to indenter diameter and indentation velocity. On the other hand, the EAM potential function of Ravelo et al [23] has been tested during nanoindentation [13] as well as shock compression experiments [23] and the outcome suggests that this potential function is better in predicting the high pressure and high temperature phases of Ta. Since the intent of this work is to understand the deformation behaviour of Ta, this study made use of an EAM potential (Ta-1) developed by Ravelo et al [23] primarily to study extreme conditions of temperature and pressure such as during nanoindentation.…”
Section: Molecular Dynamics Simulation Of Nanoindentationmentioning
confidence: 99%
“…Recent research shows that the plastic deformation in tantalum start with twins, which transforms to shear loops and eventually to prismatic loops whereby the screw components of the shear loop cross-slip and pinch out a prismatic loop in a "lasso" action [13]. Biener et al [1] performed nanoindentation experiments on the (010), (110) and (111) Attributing this as a general trend to all the BCC materials, they speculated that the (010) orientation of Ta is a typical example of surface which shows dislocation multiplication process, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Однако при h < 50−100 nm расчетная величина ρ, следующая из этой модели, становится нереалистично большой (> 10 16 m −2 ). Ав-торы работ [6,7,[42][43][44] объясняют возникновение ISE в микрообласти уменьшением размера зоны деформи-рования до некоторого характерного размера микро-структуры. В общем случае возможны и другие при-чины возникновения ISE в твердости.…”
Section: результаты и их обсуждениеunclassified
“…Consistent with bcc slip systems, the shear loops grow by the advance of their edge components while the screw components undergo limited cross-slip. Eventually the screw segments may annihilate each other since they have dislocation lines with opposite signs, and a prismatic loop is pinched off [32,33]. Figure 1 presents a side view of the indentation of a (001) Ta single crystal by an 8 nm diameter spherical indenter to a penetration of 5 nm, and a detailed view of a prismatic loop produced in the process.…”
Section: Bcc Metalsmentioning
confidence: 99%
“…Remington et al [32] presented a comprehensive nanoindentation MD study of Ta single crystals along the three principal crystallographic orientations. They reported that after the formation and annihilation of planar defects similar to the ones reported by Alcalá et al [31], shear loops form and propagate along 111 directions.…”
Section: Bcc Metalsmentioning
confidence: 99%